2004
DOI: 10.1016/s0939-4753(04)80012-7
|View full text |Cite
|
Sign up to set email alerts
|

Body fat and C-reactive protein levels in healthy non-obese men

Abstract: Previous studies have demonstrated that circulating levels of C-reactive protein (CRP), a marker of cardiovascular risk, are strictly related to body fatness. Elevated fibrinogen levels are also predictive of future cardiovascular events. The metabolic background of this relationship and the predictors of fibrinogen levels have not been well established. We aimed to evaluate whether fibrinogen levels are associated with body fat content and distribution and to determine the independent predictors of fibrinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…In their study, Bo et al observed a significant correlation between the total content of adipose tissue and the CRP level in healthy subjects [20]. Our results agree with those findingswe have found that there are significant positive correlations between the total adipose tissue volume and the CRP level in both men and women.…”
Section: Tabela IV Stężenia Interleukiny 18 (Il-18) Interleukiny 6 supporting
confidence: 93%
“…In their study, Bo et al observed a significant correlation between the total content of adipose tissue and the CRP level in healthy subjects [20]. Our results agree with those findingswe have found that there are significant positive correlations between the total adipose tissue volume and the CRP level in both men and women.…”
Section: Tabela IV Stężenia Interleukiny 18 (Il-18) Interleukiny 6 supporting
confidence: 93%
“…The clinical picture often is ambiguous [9], and although biomarkers like C-reactive protein (CRP) or leukocyte levels [4, 7, 9-11, 28, 34] are helpful, they can be misleading in patients with chronic inflammatory diseases, obesity, metabolic syndrome, and insulin resistance, and in smokers [3,4,27] and patients with postoperative hematomas [11,22].…”
Section: Introductionmentioning
confidence: 99%
“…This correlation between cf-DNA and CRP suggests that cf-DNA may be a valuable indicator of inflammation. CRP has been shown to be related to BF% in a variety of populations, including healthy non-obese individuals [26,27,28]. Practitioners should use caution when interpreting these results, as substantial individual differences may exist despite the correlation between mean values.…”
Section: Discussionmentioning
confidence: 99%